A New Way Forward for Teaching Science: A Report on the Future of the Teaching Science Journal - Sheffield, Rachel; Smith, Julie-Anne; Quinton, Geoff; Glistak, John; Treagust, David (2018)
The Executive of the Australian Science Teachers Association is considering strategic options for the future of their journal, Teaching Science. ASTA Executive asked the research team to initiate the work around this; the first stage being a 'landscape survey' of some of the factors that need to be considered when reviewing the future of the publication and achieving maximum benefit to the members of the state and territory science teachers associations.